Metabolic syndrome in relation to Barrett⿿s esophagus and esophageal adenocarcinoma: Results from a large population-based case-control study in the Clinical Practice Research Datalink. (June 2016) - Drahos, Jennifer; Li, Lin; Jick, Susan S.; Cook, Michael B.
Highlights: ⿢ Metabolic syndrome (MetS) increased risk of Barrett⿿s esophagus (BE). ⿢ GERD modified the association with increased risk confined to those without reflux. ⿢ No association between MetS and risk of EA was detected. ⿢ MetS may represent a reflux-independent inflammatory pathway that increases BE risk. Abstract: Gastroesophageal reflux disease (GERD) causes local chronic inflammation that increases risks of Barrett⿿s esophagus (BE) and esophageal adenocarcinoma (EA), yet symptomatic GERD is absent in approximately half of all such patients. Obesity exacerbates GERD and is also a component of metabolic syndrome (MetS). We evaluated the hypothesis that MetS is a GERD-independent mechanism by which obesity is associated with increased risks of BE and EA using data from the UK Clinical Practice Research Datalink. BE cases ( n  = 10, 215) and EA cases ( n  = 592) were each individually matched to five population controls based on age, sex, and general practice. MetS was defined as occurrence of at least three of the following: obesity, type 2 diabetes, hypertension, and high cholesterol. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using conditional logistic regression. MetS was marginally associated with BE (OR = 1.12, 95%CI 1.00⿿1.25). Similar effects were found for the individual component factors of obesity, hypertension, and high cholesterol. History of GERD modified the association (P -effect modification <1E⿿5), with the MetS-BE association confined to patients without a history of GERD (OR = 1.33, 95%CI 1.12⿿1.58). No association between MetS and risk of EA was detected in the main or stratified analyses. In this large population-based case-control study, individuals with MetS had a marginally increased risk of BE in the absence of GERD. The systemic inflammatory state (MetS) may represent a reflux-independent inflammatory pathway that increases the risk of BE. MetS did not increase risk of EA in this study population.